Application of the SARIMA Method in the Step Function Intervention to Predict the Number of Visitors at Londa Tourism Object - Geovani Christie; Djoni Hatidja; Rinancy Tumilaar (Jurnal Ilmiah Sains, 2022)
The object of this study are to determine the intervention model of the number of visitors at the Londa tourism object and predict the number of visitors at the Londa tourism object for December 2021 to June 2020 using Seasonal Autoregresive Integrated Moving Average (SARIMA) models. The data used is monthly data for the period from January 2018 to November 2021, which was obtained from the manager of the Londa tourist object. The data pattem on the number of visitors at the Londa tourism object experienced significant fluctuations on April 2020 (T=28). The suspected intervention model is a step function because the effect of the intervention that occurred took place over a long period of time, from April 2020 to November 2021 (T=28 to T=47). The best model obtained from the results of data analysis is SARIMA (1,1,0)(1,1,0)[6] with an intervention order of b=0, s=5, and r=2, with MAPE and MAE values are 4,38% and 0,397.  Forecasting results from December 2021 to June 2022 respectively, are 2550, 756, 347, 515, 1585, 1287 and  2247 people.  The number of visitors will increase during the holiday season, i.e. December and June.Keywords: Intervention model; Londa tourism object; step functionPenerapan Metode SARIMA dalam Model Intervensi Fungsi Step untuk Memprediksi Jumlah Pegunjung Objek Wisata LondaABSTRAKTujuan dari penelitian ini yaitu menentukan model intervensi pada data jumlah pengunjung di objek wisata Londa dan memprediksi jumlah pengunjung objek wisata Londa pada bulan Desember 2021 sampai Juni 2022 menggunakan model Seasonal Autoregresive Integrated Moving Average (SARIMA). Data yang digunakan adalah data jumlah pengunjung bulanan pada periode bulan Januari 2018 sampai bulan November 2021, yang diperoleh dari pihak pengelolah objek wisata Londa.  Pola data jumlah pengunjung pada objek wisata Londa mengalami fluktuasi yang signifikan, yaitu pada bulan April 2020 (T=28). Model intervensi yang digunakan dalam penelitian ini yaitu fungsi step karena pengaruh yang terjadi berlangsung dalam kurun waktu cukup lama yaitu pada bulan April 2020 sampai November 2021 (T=28 sampai T=47).  Model terbaik yang diperoleh dari hasil analisis data yaitu SARIMA (1,1,0)(1,1,0)[6] dengan orde intervensi b=0, s=5, dan r=2, dengan nilai MAPE dan MAE masing-masing sebesar 4,38% dan 0,397.  Hasil prediksi dari bulan Desember 2021 sampai Juni 2022 secara berturut-turut yaitu 2550, 756, 347, 515, 1585, 1287 dan 2247 orang.  Jumlah pengunjung akan meningkat pada waktu musim liburan yaitu Bulan Desember dan Juni.Kata kunci: Model intervensi; fungsi step; objek wisata Londa,